Divine Election and Sacred Familyhood: Reinterpreting the Narrative of the Family of Imrān in the QS. Āli ‘Imrān [3]: 33–37 - Ahmad Bastari (Jurnal Semiotika Quran, 2026)
This study aims to reinterpret the narrative of Imrān's family in QS. Āli ‘Imrān [3]: 33–37. Among several families mentioned as God's chosen ones, Imrān's family occupies an important theological position because it represents a family model that was formed through divine selection and built on the foundations of spirituality, devotion, and religious education. Using a qualitative approach with the tahlīlī interpretation method, this study re-examines the narrative of Imrān's family as a normative construction of a family that obtains spiritual legitimacy through divine will. The results of the study show that the selection of the family of Imrān in the Qur'an is not solely based on biological lineage, but rather on spiritual qualities, commitment to worship, and an educational orientation centered on piety towards Allah SWT. Divine selection of the family of Imrān is reflected through their transcendent vision, the practice of prayer as the foundation of education, the selection of a pious educational environment, and the maintenance of noble character in family life. Thus, the family of Imrān can be understood as a Qur'anic family paradigm that integrates theological, moral, and pedagogical dimensions. These values remain relevant to Muslim families today as a model for family formation based on piety, spiritual consistency (istiqāmah), and the internalization of Islamic values in modern social life.